Safety and Efficacy of Mini Percutaneous Nephrolithotomy in Paediatric age Patients: Paving the Way Towards Minimally Invasive Techniques in Resources Limited Areas - Tariq Ahmad, Muhammad Asif, Farman Ullah Khan, Muhammad Asif Ammar, Asif Khan, Nasrum Minallah (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To assess the safety and effectiveness of mini-percutaneous nephrolithotomy (PCNL) in paediatric age patients. Materials and Methods: This descriptive case series study was conducted in the Department of Paediatric Urology, Institute of Kidney Diseases, Hayatabad Medical Complex, Peshawar, Pakistan from June 2017 to June 2020. Children < 14 years, diagnosed with renal stone > 1cm in size on non-contrast CT of Kidney Ureter and Urinary Bladder (KUB) and having negative urine culture were enrolled in the study. Patients having abnormal renal functions and bleeding diathesis were omitted from the study. Informed written consent was taken from the parents of all the children. Children with no stone fragments in the kidney or ipsilateral ureter on non-contrast CT KUB at one month were labelled as stone free. Results: A total of 213 children who underwent mini-PCNL were analyzed. 130 (61.03%) of the stones were 10-15 mm and 83 (38.97%) were > 15 mm in size. The mean operation time was 56.02 + 7.82 (40-81) minutes .The mean hospital stay was 2.22 + 0.67 (2-7) days. The mean decrease in haemoglobin was 1.30 + 0.67 (0.2-4.0) gm/dL. No major intraoperative complication was observed. 24 (11.27%) of the patients developed post-operative complications including 10.33 % minor and 0.94 % major complications which were statistically insignificant. As a monotherapy mini-PCNL achieved complete stone clearance at one month in 191 (89.67%) of the patients. Retreatment was required in 22 (10.33%) of the patients including extracorporeal shock wave lithotripsy (ESWL) in 7 (3.29%), ureteroscopy (URS) in 10 (4.69%) and Re-PCNL in 5 (2.35%) patients. Conclusion: This study concludes that mini-PCNL in a paediatric population is safe and effective for renal stones > 10 mm with acceptable stone clearance and complications. Keywords: Kidney calculi, Pediatrics, Percutaneous, Children, Urolithiasis